Earth follies - Seager, Joni. (New York : Routledge, 1993)
What can feminists contribute to our understanding of environmental problems? Does it matter that the institutions that control our environmental fate are constructs of male culture? We have so polluted the earth, so degraded our environment, and so disrupted our biosphere that the continued existence of life on the planet is at risk. but "we" - an undifferentiated humanity - have not done so. Most of the really large-scale environmental problems - not litter on the streets, but the environmental disruptions that might kill us all - are the products of very powerful institutions that control the state of our environment, including prominently militaries, multinationals, and governments. And overwhelmingly, these institutions are controlled by men.
Earth Follies offers a powerful argument for looking at "agency" in understanding our environmental affairs. The environmental crisis is not just the sum of ozone depletion, global warming, and overconsumption. It is a crisis of culture precipitated by the institutions that shape modern life. Seager offers a provocative and original feminist analysis of the crisis that focuses on the structures of power within these institutions and the ways in which they are dominated by masculinist presumptions. Seager demonstrates that the implications and experiences of environmental decay are often different for men and women, rich and poor, elites and disenfranchised. Environmental relations are inextricable from the larger gender relations that shape modern life and this fact makes a feminist analysis of our environmental state absolutely crucial.
Earth Follies avoids essentialist notions about the "inherent natures" of men and women and even enters the lively debate about eco-feminism and the complicated historical relationship between "woman" and "nature." In addition, the book takes a careful look at the environmental movement and the organizations which have grown from it while critiquing their policies and programs and the masculinist presumptions which are frequently responsible for shaping them. From Bhopal to the Pacific Islands, from the Amazon rainforests to our backyards, Seager exposes some of the factors that link local environmental disasters to produce global crisis. She makes clear that the politics of gender; usually intertwined with the politics of racism, lie just beneath the environmental surface.
Earth Follies pulls no punches, but Seager demonstrates that there is too much at stake to stick to easy questions. In marking out the territory for an environmental analysis informed by feminist politics, the book provides one of the most powerful analyses to date of the crisis that stands before us, as well as proposing new and productive priorities for the environmental agenda.
Keywords: Environmental policy; Human ecology; Feminist theory